Tissue engineering and biosensing applications of carbon-based nanomaterials - Seydanur Yücer; Begüm Sarac; Fatih Ciftci (Biomedical Engineering Advances)
Carbon nanomaterials (CNMs) have emerged as a transformative class of materials in the biomedical field, offering exceptional versatility and efficacy. This study highlights the unique mechanical, electrical, and biocompatible properties of CNMs that make them indispensable for applications such as drug delivery, biosensing, tissue engineering, and medical implants. Specifically, graphene's remarkable conductivity and mechanical strength enhance biosensor sensitivity and scaffold durability, while the tubular structure and functional surface chemistry of carbon nanotubes (CNTs) improve cellular interactions and mechanical stability in implants. Carbon dots, with their tunable fluorescence and high biocompatibility, are proving to be powerful agents for bioimaging, enabling more precise diagnostics.This review consolidates recent advancements in the synthesis, functionalization, and biomedical integration of CNMs, emphasizing their role in next-generation applications. Notably, it addresses challenges related to scalable production and clinical safety, offering insights into overcoming these obstacles. The findings underline the transformative potential of CNMs in revolutionizing therapeutic and diagnostic approaches, paving the way for innovative solutions in healthcare.